LOKASI INFARK BERDASARKAN VASKULARISASI SEBAGAI FAKTOR PROGNOSIS OUTCOME FUNGSIONAL STROKE INFARK - , Nida'ul Khasanah ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: The WHO defines stroke as rapidly developing clinical signs of focal (at times global) disturbance of cerebral function, lasting more than 24 hours or leading to death with no apparent cause other than of vascular origin. In Indonesia, stroke is the leading death cause in hospitals and community and a major cause of disability. Its prevalence in Indonesia is increasing due to the life style changes. Eighty-five percent cases are due to cerebral infarction and others are to hemorrhage. Nowadays, head computed tomography is routinely performed in many hospitals for cerebrovascular disseases to confirm clinical diagnosis of stroke and to differentiate its type. Outcome of stroke generally describe as death rate and functional status. Post stroke functional status assesed in most studies used Barthel Index and Modified Rankin Scale (mRS). Only few studies have been performed to investigate the role of brain infarction locations to the outcome. Based on the vascularitation, location of brain infarctions are divided into total anterior (TACI), partial anterior (PACI), lacunar (LACI) and posterior (POCI). Materials and Methods: This study is a non experimental observational cohort study. The study population consisted of 54 patients with infarct stroke that admitted to Stroke Unit and Neurology ward of Dr. Sardjito Central General Hospital from Oktober 2011 to Januari 2012, according to inclusion and exclusion criteria. Collected data was proccessed and statistically analized using X2 Result. Infarc TACI tipe significantly has BI score lower than the other three tipes of infarct in one month observation (p= 0,006). And in disability matter from PACI, LACI and POCI statistically not significant. In univariable analysis there are other factor influence stroke outcome : infarc measurement and first BI score, and in multivariate analysis only the infarct location is significant test and oneway anova with p < 0.05. Other prognostic factors for functional outcome of infarct stroke was analized using logistic regression test. Conclusion : Location of infarction based on vascularitation has role in infarct stroke outcome